2018
DOI: 10.1016/j.ajur.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Present indications and techniques of percutaneous nephrolithotomy: What the future holds?

Abstract: The purpose of the review was to present the latest updates on percutaneous nephrolithotomy (PCNL) procedure in terms of indications and evolving techniques, and to identify the advantages and disadvantages of each modality. The data for this review were collected after a thorough PubMed search in core clinical journals in English language. The key words included “PCNL” and “PNL” in combination with “indications”, “techniques”, “review” and “miniaturized PCNL”. Publications relevant to the subject were retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…1 The altered orientation of the kidney can make stone removal by percutaneous nephrolithotomy (PCNL) difficult, but studies have also shown that it can be a safe procedure as long as careful preoperative and postoperative planning is undertaken. [2][3][4] Alternatively, pyelolithotomy may be considered, which can take advantage of the anterior facing renal pelvis, but is more invasive and morbid, with concomitant risk for abdominal injury. Other viable options for stone removal in malrotated kidneys include flexible ureteroscopic lithotripsy and mini-PCNL; however, because of the significantly large stone burden, severe hydronephrosis, and anatomic complexity of our patient, these methods were not pursued further.…”
Section: Discussionmentioning
confidence: 99%
“…1 The altered orientation of the kidney can make stone removal by percutaneous nephrolithotomy (PCNL) difficult, but studies have also shown that it can be a safe procedure as long as careful preoperative and postoperative planning is undertaken. [2][3][4] Alternatively, pyelolithotomy may be considered, which can take advantage of the anterior facing renal pelvis, but is more invasive and morbid, with concomitant risk for abdominal injury. Other viable options for stone removal in malrotated kidneys include flexible ureteroscopic lithotripsy and mini-PCNL; however, because of the significantly large stone burden, severe hydronephrosis, and anatomic complexity of our patient, these methods were not pursued further.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in PCNL techniques included not only decrease of the working instruments diameter but also improvement of patient positioning, safer and more accurate tract creation techniques, new imaging modalities, evolvement of intracorporeal lithotripters and incorporation of flexible instruments for efficient collecting system screening (Sabler et al, 2018).…”
Section: Disadvantages Of Mini-pcnlmentioning
confidence: 99%
“…Kidney stones such as brushite (a unique calcium phosphate stone), calcium oxalate monohydrate and cystine should be treated by pre-operative percutaneous nephrolithotripsy (PCNL) or retrograde intrarenal surgery (RIRS) ( 12 ). Dual-energy computed tomography (DECT) is a reliable method to determine kidney stone composition in vivo ( 13 16 ) and in vitro ( 17 – 20 ).…”
Section: Introductionmentioning
confidence: 99%